2000
DOI: 10.1073/pnas.97.11.5889
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum retention is a common defect associated with tyrosinase-negative albinism

Abstract: Tyrosinase is a melanocyte-specific enzyme critical for the synthesis of melanin, a process normally restricted to a post-Golgi compartment termed the melanosome. Loss-of-function mutations in tyrosinase are the cause of oculocutaneous albinism, demonstrating the importance of the enzyme in pigmentation. In the present study, we explored the possibility that trafficking of albino tyrosinase from the endoplasmic reticulum (ER) to the Golgi apparatus and beyond is disrupted. Toward this end, we analyzed the comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
160
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(176 citation statements)
references
References 51 publications
15
160
0
1
Order By: Relevance
“…This prediction was based in part on the colocalization of p with mutated Tyr in melan-c cells, which was assumed at the time to be situated in melanosomes, but to be enzymatically inactive. It has since been shown that the mutated Tyr in melan-c cells is in fact trapped in the ER and subsequently degraded (Halaban et al, 2000b). Indeed, the colocalization of Tyr and p in melan-c cells further strengthens our conclusions regarding the ER localization of p. However, it is still possible that a portion of total p may locate in other organelles.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…This prediction was based in part on the colocalization of p with mutated Tyr in melan-c cells, which was assumed at the time to be situated in melanosomes, but to be enzymatically inactive. It has since been shown that the mutated Tyr in melan-c cells is in fact trapped in the ER and subsequently degraded (Halaban et al, 2000b). Indeed, the colocalization of Tyr and p in melan-c cells further strengthens our conclusions regarding the ER localization of p. However, it is still possible that a portion of total p may locate in other organelles.…”
Section: Discussionsupporting
confidence: 48%
“…Densitometric analysis revealed that approximately one-third of Tyr in melan-p1 cells is in this form. This form of Tyr was found to comigrate with Tyr from melan-c cells, derived from a mouse homozygous for point mutations in Tyr, which results in ER retention of Tyr (Halaban et al, 2000b).…”
Section: A Higher Percentage Of Tyr Is Retained In Er Of Melan-p1 Celmentioning
confidence: 99%
See 1 more Smart Citation
“…Trafficking defects are usually caused by the inability of the mutant protein to correctly fold and pass ER quality control system, and thus by its subsequent degradation (Cobbold et al, 2003;Sitia and Braakman, 2003). Incubation at permissive temperature typically rescues several of these misprocessed proteins (Denning et al, 1992;Payne et al, 1998;Halaban et al, 2000;Valdivia et al, 2002;Anderson et al, 2006). This has been interpreted as a kinetic effect because of more functional proteins able to correctly fold and escape the quality control of the ER because of the slowed kinetics of folding (Bernier et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic Labeling-Pulse-chase experiments were performed as described previously (8). Cells were pulse-labeled for 15 min with [ 35 S]Met/Cys (0.7 mCi/ml, EasyTag, PerkinElmer Life Sciences) in methionine/cysteine-free RPMI 1640 medium (Invitrogen) and either collected immediately or after chase incubation with non-radioactive medium (Ham's F-10 medium) for the indicated period of time.…”
Section: Methodsmentioning
confidence: 99%